2021
DOI: 10.36227/techrxiv.15141537.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability-Aware Design of Spike-Event Neuromorphic Circuits

Abstract: Very Large Scale Integration (VLSI) based neuromorphic circuits also known as Silicon Neurons (SiNs) emulate the electrophysiological behavior of biological neurons. With the advancement in technology, neuromorphic systems also lead to various reliability issues and hence making their study important. Bias Temperature Instability (BTI) and Hot Carrier Injection (HCI) are the two major reliability issues present in VLSI circuits. In this work, we have investigated the combined effect of BTI and HCI on the two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…A reduction in V TH shift can be achieved by employing a rel-SLIF neuron in place of the conv-SLIF neuron. 40 In the rel-SLIF neuron circuit, a diode-connected transistor PM4 is added to mitigate degradation in transistor PM1. Figure 11 shows rel-SLIF neuron.…”
Section: Reliability-aware Temporal Neuromorphic Encodermentioning
confidence: 99%
See 2 more Smart Citations
“…A reduction in V TH shift can be achieved by employing a rel-SLIF neuron in place of the conv-SLIF neuron. 40 In the rel-SLIF neuron circuit, a diode-connected transistor PM4 is added to mitigate degradation in transistor PM1. Figure 11 shows rel-SLIF neuron.…”
Section: Reliability-aware Temporal Neuromorphic Encodermentioning
confidence: 99%
“…It is reported that the rel-SLIF neuron consumes less power than the conv-SLIF neuron. 40 This is because the addition of the transistor PM4 lowers the voltage swing of the inverter output, which reduces the power consumption.…”
Section: Reliability-aware Temporal Neuromorphic Encodermentioning
confidence: 99%
See 1 more Smart Citation